A randomized, multicenter, phase III study of gemcitabine combined with capecitabine versus gemcitabine alone as first-line chemotherapy for advanced pancreatic cancer in South Korea. Issue 1 (January 2017) - Lee, Hee Seung; Chung, Moon Jae; Park, Jeong Youp; Bang, Seungmin; Park, Seung Woo; Kim, Ho Gak; Noh, Myung Hwan; Lee, Sang Hyub; Kim, Yong-Tae; Kim, Hyo Jung; Kim, Chang Duck; Lee, Dong Ki; et al.
Abstract: Background: This phase III trial compared the efficacy and safety of gemcitabine plus capecitabine (GemCap) versus single-agent gemcitabine (Gem) in advanced pancreatic cancer as first-line chemotherapy. Methods: A total of 214 advanced pancreatic cancer patients were enrolled from 16 hospitals in South Korea between 2007 and 2011. Patients were randomly assigned to receive GemCap (oral capecitabine 1660 mg/m 2 plus Gem 1000 mg/m 2 by 30-minute intravenous infusion weekly for 3 weeks followed by a 1-week break every 4 weeks) or Gem (by 30-minute intravenous infusion weekly for 3 weeks every 4 weeks). Results: Median overall survival (OS) time, the primary end point, was 10.3 and 7.5 months in the GemCap and Gem arms, respectively ( P  = 0.06). Progression-free survival was 6.2 and 5.3 months in the GemCap and Gem arms, respectively ( P  = 0.08). GemCap significantly improved overall response rate compared with Gem alone (43.7% vs 17.6%; P  = 0.001). Overall frequency of grade 3 or 4 toxicities was similar in each group. Neutropenia was the most frequent grade 3 or 4 toxicity in both groups. Conclusion: GemCap failed to improve OS at a statistically significant level compared to Gem treatment. This study showed a trend toward improved OS compared to Gem alone. GemCap and Gem both exhibited similar safety profiles. Abstract : Supplemental Digital Content is available in the text